Classifying the Variety of Drug Trafficking Organizations. (October 2015) - Natarajan, Mangai; Zanella, Marco; Yu, Christopher
A standard typology of drug trafficking organizations would assist in interpreting the results of studies made of these organizations. Several such typologies have been proposed, and this study examines a widely cited typology that was developed in the 1990s using New York City court data. The typology has two dimensions, organizational tasks and structure. It satisfactorily encompassed the trafficking organizations identified in two new samples: 39 organizations prosecuted in New York City in 1997-2007 and 50 organizations prosecuted during the same period by the Drug Enforcement Administration. The findings supported the generalizability of the typology. They also suggest that drug trafficking organizations adopt a structure congruent with their external environment, including the market for drugs, the type of drugs, ethnicity of those involved in distribution, use of technology in communication and distribution, and levels of law enforcement. Implications of fuller knowledge about the structure and functioning of drug trafficking organizations for research and policy are discussed.